AKIBAT PELANGGARAN OLEH NOTARIS TERHADAP PEMBUATAN AKTA NOTARIIL - Lorika Cahaya Intan (Jurnal Cakrawala Hukum, 2016)
The problem that will be discussed in this research is whether the deed made before the notary is legally valid, in case of violation of Article 16 Paragraph (1) Letter (a) of Notary Position Law, how the Notary’s responsibility to the deed already issued by a notary if it does not implement Article 16 Paragraph (1) Subparagraph (a) of the Notary Position Law. The research method used is normative. Based on the result of research in the validity of the deed made before the notary in case of violation of Article 16 Paragraph (1) Subparagraph (a) of Law on Notary Position, as the case of transition or sale and purchase of building on Malang City Government land. Found a deed made by a notary, and has been issued by a notary, in case of violation of Article 16 Paragraph (1) Letter (a) Law on the position of Notary, legally valid. Sanctions only affect the legal subject of a Notary pursuant to Article 16 paragraph (11) that is subject to sanctions in the form of written warning, suspension, dismissal with respect; or dismissal with disrespect.